АВТОМАТИЗОВАНІ НАВЧАЛЬНІ СИСТЕМИ ЯК ОСНОВНИЙ КОМПОНЕНТ ІНТЕГРАЦІЇ ПЕДАГОГГЧНИХ ТА ІНФОРМАЦІЙНИХ ТЕХНОЛОГІЙ (Педагогіка вищої та середньої школи, 2007)
The essence of the notion of automatized learning system has been revealed in the article, the basic attention being paid to the peculiarities of its application in teaching pupils of secondary schools. The most important principles of automatized learning systems implementation have been defined. An attempt to point out the general components of such systems has been made.